2017
DOI: 10.1007/s10354-017-0612-0
|View full text |Cite
|
Sign up to set email alerts
|

Spicae aetheroleum in uncomplicated acute bronchitis: a double-blind, randomised clinical trial

Abstract: SummaryBackground The trial aimed to evaluate the efficacy and safety of Spicae aetheroleum (Spicae ae.), a phytomedicine obtained by steam distillation of the flowering tops of Lavandula latifolia, as compared to placebo in adult patients with acute bronchitis. Methods Patients with uncomplicated acute bronchitis (bronchitis severity score [BSS] ≥ 5 score points) were randomly assigned to treatment with Spicae ae. or placebo in a double-blind, parallel-group design. No additional treatment was admitted. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…In a double-blind, placebo-controlled RCT cineole was significantly more effective for timely treatment of nonpurulent rhinosinusitis in 150 patients (24) . To date, one placebocontrolled RCT examined the efficacy and safety of Tavipec® in acute RTIs: Kähler et al administrated 300 mg Tavipec® three times daily to 256 patients with uncomplicated acute bronchitis (28) . The treatment with Tavipec® exhibited a significant mean difference of 25% of a defined total bronchitis severity score (BSS) between verum and placebo after 7 (p<0.005) and 10 days (p<0.009) of full medication as well as a significant amelioration of the patients' QoL (p<0.001) as compared to placebo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a double-blind, placebo-controlled RCT cineole was significantly more effective for timely treatment of nonpurulent rhinosinusitis in 150 patients (24) . To date, one placebocontrolled RCT examined the efficacy and safety of Tavipec® in acute RTIs: Kähler et al administrated 300 mg Tavipec® three times daily to 256 patients with uncomplicated acute bronchitis (28) . The treatment with Tavipec® exhibited a significant mean difference of 25% of a defined total bronchitis severity score (BSS) between verum and placebo after 7 (p<0.005) and 10 days (p<0.009) of full medication as well as a significant amelioration of the patients' QoL (p<0.001) as compared to placebo.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory properties and mode of action (MoA) of plant derived monoterpenes as well as their efficacy to control signs and symptoms of RTIs including viral ARS have been thoroughly investigated (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) . Monoterpenes are resorbed in the gastrointestinal tract and enter the circulation and reach the mucosal secretory glands, where they have secretolytic effects by enhancing mucus production and ciliary beat frequency (CBF) as well as stimulating ciliary cell differentiation, thus supporting the cleaning function and the recovery process of the mucosa (14,15,22,30,31) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of bias (RoB) of study findings was assessed using the revised Cochrane RoB tool for randomised trials (RoB 2) https://sites.google.com/site/riskofbiastool/welcome/rob-2-0-tool/current-version-of-rob-2 (see Supplement 2). In the first domain (randomisation process), all trials were rated as low risk of bias [ [1] , [2] , [3] , [4] , [5] , 7 , 8 ]. For domain 2 (treatment assignment), all trials were rated as low risk of bias [ [1] , [2] , [3] , [4] , [5] , 7 , 8 ].…”
Section: Search Strategymentioning
confidence: 99%
“… Verdict Clinical evidence from published clinical trials identified in this rapid review suggests that oral administration of blends of certain essential oils (EO) can reduce symptoms of acute respiratory infections of viral origin in humans, namely acute sinusitis and acute bronchitis. There is clinical evidence for orally administered Lavandula latifolia essential oil (Tavipec®) (n = 2) and a blend of essential oils of Eucalyptus globulus , Citrus sinensis , Myrtus communis and lemon Citrus limonum (Myrtol® and its successors GeloMyrtol® and GeloMyrtol®Forte) (n = 3) to reduce symptoms of acute sinusitis and acute bronchitis of viral origin(s) [ [1] , [2] , [3] , [4] , [5] ]. All five clinical trials relied mostly on (subjective) symptom scores to determine the treatment effect.…”
mentioning
confidence: 99%